Impact of Electronic Prescribing of Controlled Substances on Opioid Prescribing: Evidence From I-STOP Program in New York. (February 2022) - Pylypchuk, Yuriy; Parasrampuria, Sonal; Smiley, Carmen; Searcy, Talisha
New York's Internet System for Tracking Over-Prescribing (I-STOP) Act, requires prescribers in the state to electronically prescribe controlled substances (EPCS). We examine the effects of this mandate on prescribing patterns of opioids for Medicare Part D beneficiaries. Using 2014-2017 CMS Medicare Part D Prescriber Data, we apply a lagged dependent variable regression approach to identify the impact of I-STOP on the prescription of opioids. In the first year of implementation, the number of opioid prescriptions per prescriber decreased by 5.7 per year. The policy had a larger effect on the prescription of short-acting opioids and on prescribers prescribing medication for predominantly younger beneficiaries. Overall, I-STOP resulted in a reduction in the number of beneficiaries being prescribed opioids and in the number of opioid claims in the state of New York, suggesting positive implications for other states intending to curtail opioid overprescribing and misuse through the use of EPCS.